A new endemic species of Cerastium (Caryophyllaceae) from Iran - Poursakhi, Katayoun; Assadi, Mostafa (Phytotaxa, 2017)
Cerastium cylindricum sp. nov. from Tehran (Iran) is here described and illustrated as a new species for science. Macro- and micromorphological characteristics in comparison with the related C. dichotomum, as well as a full description and distribution of the new taxon are provided. Ultrastructure of the seeds was examined using SEM.